Analysis of the structure and evolution of poverty in Costa Rica - Rodríguez Soto, Jorge Andrés (2023)
In Costa Rica, poverty is typically characterized as structural. This paper investigates the structure and evolution of poverty from 2010 to 2021. The analysis begins by reviewing main conceptions of development, their specific definitions of poverty, and the indicators linked to those definitions. Using poverty lines and the multidimensional poverty index (MPI) as tools, the research evaluates poverty by dimension, indicator, and region. The findings indicate that regional disparities in poverty appear more quantitative than qualitative, suggesting similar deprivation structures across areas. Regions are classified into three distinct MPI patterns: the Central region with superior conditions, an intermediate group, and the Huetar regions with more challenging conditions. An additional study of cantonal data offers a short-term perspective, further validating these identified trends. The research concludes by suggesting recommendations for the elaboration of public policies to address poverty effectively.